A Wireless Pressure Microsensor Fabricated in HTCC Technology for Dynamic Pressure Monitoring in Harsh Environments. (14th January 2015) - Gao, Ronghui; Hong, Yingping; Zhang, Huixin; Liu, Wenyi; Liang, Ting; Zhang, Wendong; Xiong, Jijun
Abstract : The partially stabilized zirconia (PSZ) ceramic has wide applications due to its excellent mechanical toughness and chemically inert and electrical properties for fabricating various devices. In this paper, a novel high temperature pressure sensor with the PSZ was designed and fabricated. The sensor was designed based on the small deflection theory, which enables its theoretic pressure-capacitance capability up to 60 bar. HTCC process technology was used to fabricate the sensor, which would realize a completely passive LC resonant circuit integrated on the ceramic substrate. According to the coupling principle, noncontact testing is achieved using the designed readout system, with average sensitivity up to 38 kHz Bar −1 presented. Compared to the fabrication and measurement of traditional sensors, excellent packaging process is demonstrated, and the sensor can be completely tested from 0 to 60 bar.